A spectroscopy approach for the study of the interactions of bioactive vanadium species with bovine serum albumin - Ferrer, Evelina Gloria (2008)
The interest in biological functions (benefits or toxics effects) of vanadium species has grown enormously in recent years. In this work, different spectroscopic methods were applied to study the effects of the interaction of vanadyl and vanadate species with bovine serum albumin (BSA), considered as the most abundant plasma protein. UV-Vis, Fourier transform infrared (FT-IR), and FT-Raman spectroscopies were used to investigate changes in secondary and tertiary structures of BSA induced by the binding of oxovanadium(IV) and vanadate(V) species (VO2+ and VO3-, respectively). Correlations between the metal ion binding mode, protein conformational transitions, and structural variations were established.